2003
DOI: 10.1258/000456303321016196
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy in childhood leukaemia: in vitro studies of thiopurines and inhibitors of purine metabolism on apoptosis

Abstract: The results of this study indicate that sequential administration of MTX before 6MP and of TF before TG may be essential for therapeutic success in the treatment of leukaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
1
Order By: Relevance
“…Because 6-TG is a purine antimetabolite, with activity against lymphoproliferative diseases [ 27 , 28 ], we investigated its effect on cell survival in CLGL-90. Both 6-TG and Zeb have a dose-dependent and cumulative effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Because 6-TG is a purine antimetabolite, with activity against lymphoproliferative diseases [ 27 , 28 ], we investigated its effect on cell survival in CLGL-90. Both 6-TG and Zeb have a dose-dependent and cumulative effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…We have examined the induction of cell death by combinations of 6-MP and MTX in MOLT-F4 cells [55]. We observed that MTX and 6-MP induced apoptosis and that sequential exposure to MTX for 24 h followed by 4 h exposure of 6-MP showed a synergistic induction of apoptosis compared with single drug exposure.…”
Section: In Vitro Studies Of Inhibitors Of Thiopurines/purine Metabolmentioning
confidence: 98%
“…56,57) In addition, 6-thioguanine, another metabolite, is frequently used in the treatment of leukemia. 58,59) Chlordiazepoxide Chlordiazepoxide was thê rst benzodiazepine derivative made available for clinical use. The drug is biotransformed to pharmacologically active products such as desmethylchlordiazepoxide, demoxepam, desmethyldiazepam, and oxazepam.…”
Section: O-dealkylationmentioning
confidence: 99%